Using an extended technology acceptance model to determine students’ behavioral intentions toward smartphone technology in the classroom - Fuchs, Kevin (Frontiers in Education, 2022)
The modern classroom takes on numerous forms and expands beyond the traditional brick-and-mortar walls. Educators are increasingly expected to integrate ICT and e-learning into the modern classroom. Several variables may influence instructors' decision-making processes about ICT integration in the classroom. Smartphone technology provides students with accessibility, the ability to communicate with others, as well as to engage with classroom material. The study aims to examine how a variety of factors (perceived usefulness, perceived ease of use, subjective norm, and attitude) influence behavioral intention towards the use of smartphone technology. 290 survey responses were analyzed to identify the relationship between these factors based on an extended technology acceptance model. The empirical results of the study revealed that subjective norms and attitudes are significant predictors of behavioral intention toward the use of smartphone technology. The article concludes by presenting implications for educators, policymakers, and education researchers derived from the academic and practical discussions based on the findings.